No way to treat a First Lady a novel - Buckley, Christopher 1952- (Random House, 2002)
When First Lady Beth ManMann is charged with killing her philandering husband, the President of the United States, during a bedroom argument, she turns for help to notorious defense attorney Boyce "Shameless" Baylor, her former flame.
Keywords: Attorney and client -- Fiction; Presidents' spouses -- Fiction; Trials (Murder) -- Fiction; Widows -- Fiction; Legal stories